Integration of Technology and Islam-Based Curriculum in Improving School Quality - Nurrohman Nurrohman; Irfan Anshori; Sibusiso Ndlovu (Thawalib: Jurnal Kependidikan Islam, 2026)
The integration of technology and a curriculum based on Islamic values at Sekolah Menengah Kejuruan Informatika Kota Serang remains limited, with few studies that combine both to enhance education holistically. This study aims to analyze how integrating technology with an Islamic-based curriculum can improve educational quality. The research employs a qualitative case study approach, collecting data through interviews, observations, and documentation, and analyzing it through condensation, presentation, and drawing conclusions. The results indicate that technological integration through Tally, Braja, ARKAS, E-Learning, WhatsApp, and Information Technology media enhances student management, financial administration, communication, learning processes, and students’ digital skills. The Islam-based curriculum through Islamic Religious Education, Tarbiyah Islamiyah, and Islamic Gathering fosters Islamic character, a positive learning ethos, discipline, responsibility, tolerance, and social awareness. The synergy of both approaches increases student engagement, learning outcomes, critical thinking, and creativity, making the school adaptive to technology while maintaining internalization of Islamic values. In conclusion, the simultaneous integration of technology and Islamic curriculum improves education quality, student engagement, learning outcomes, and adaptive Islamic character. This study is significant as an innovative model for the development of vocational education policy and practice, combining academic and Islamic character aspects to enhance students’ creativity, problem-solving, and adaptability.